Teachers' Instructional Time Management Practices and Learners’ Academic Performance in Zone 3, Schools Division of Zambales - Dianne L. Mendigorin (Future Science / FSH-PH Publications, 2026)
Instructional time management is crucial in enhancing the teaching-learning process and improving students’ academic performance. This study examined teachers’ instructional time management practices and their relationship with learners’ academic performance in Zone III schools of the Division of Zambales. Specifically, it described the teachers’ demographic profile, assessed their instructional time management practices, and determined the extent to which these variables influenced student performance. The study addressed a research gap concerning the limited examination of how demographic characteristics affect instructional time management and its correlation with academic performance. A descriptive-correlational research design was employed using survey questionnaires and learners’ academic performance records. Results showed that most respondents were young female teachers handling intermediate grades, with adequate teaching experience and postgraduate educational backgrounds. Teachers consistently practiced instructional time management, particularly in motivating learners, while students demonstrated very satisfactory academic performance. Significant differences in instructional time management were found when teachers were grouped according to gender, age, length of service, and teaching position. However, no significant differences were observed in planning and resource management across teacher profiles. Moreover, the relationship between instructional time management and academic performance revealed a very low positive correlation. Based on the findings, the study recommends targeted development programs.